Assistance process to women with severe maternal morbidity: a mixed study - Jessica Paola Garcia Villalba; Adriana Lenho de Figueiredo Pereira; Ana Beatriz Azevedo Queiroz; Deise Breder dos Santos Batista; Juliana Cristina Nascimento Guimarães (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To describe the maternal and obstetric characteristics associated with severe maternal morbidity, and the factors of the assistance process involved in the severe outcomes according to nurses and doctors. Method: Sequential mixed study at the tertiary maternity in the city of Rio de Janeiro, based on care records and interviews with these professionals, from February to July 2019. Chi-square test, prevalence ratio and thematic content analysis were applied. Results: In 66 (100%) women with SMM, severe preeclampsia (77.3%) was more prevalent and there were 12 (18.2%) cases of near miss and one maternal death. Postpartum hemorrhage (PR = 3.21; 95% CI 1.22-8.41) and blood transfusions (PR = 3.60; 95% CI 1.81-7.16) contributed to severe outcomes. There are deficiencies in the health system, access to reproductive health and quality of care. Conclusion: Improvements in access to health and quality of the care process are imperative to reduce severe maternal outcomes.